2014
DOI: 10.1088/0268-1242/29/7/075008
|View full text |Cite
|
Sign up to set email alerts
|

Illuminated to dark ratio improvement in lateral SOI PIN photodiodes at high temperatures

Abstract: This work presents a study of the illuminated to dark ratio (IDR) of lateral SOI PIN photodiodes. Measurements performed on fabricated devices show a fivefold improvement of the IDR when the devices are biased in accumulation mode and under high temperatures of operation, independently of the anode voltage. The obtained results show that the doping concentration of the intrinsic region has influence on the sensitivity of the diodes: the larger the doping concentration, the smaller the IDR. Furthermore, the pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…The lateral dimension of nanobar is considered as 15 µm while the lateral extents of highly doped p‐type and n‐type regions are set as 0.5 µm. The dopant concentrations in n‐type and p‐type regions are chosen as N = 4 × 10 20 cm −3 and P = 1 × 10 20 cm −3 , respectively, in accordance with empirical values demonstrated in several experiments . The choice of asymmetric doping has been made to yield a more uniform carrier distribution up to 10 19 cm −3 across the intrinsic region by compensating the effect of Auger recombination which becomes prominent for carrier densities higher than 5 × 10 18 cm −3 .…”
Section: Dynamic All‐dielectric Metasurface Doubletmentioning
confidence: 99%
“…The lateral dimension of nanobar is considered as 15 µm while the lateral extents of highly doped p‐type and n‐type regions are set as 0.5 µm. The dopant concentrations in n‐type and p‐type regions are chosen as N = 4 × 10 20 cm −3 and P = 1 × 10 20 cm −3 , respectively, in accordance with empirical values demonstrated in several experiments . The choice of asymmetric doping has been made to yield a more uniform carrier distribution up to 10 19 cm −3 across the intrinsic region by compensating the effect of Auger recombination which becomes prominent for carrier densities higher than 5 × 10 18 cm −3 .…”
Section: Dynamic All‐dielectric Metasurface Doubletmentioning
confidence: 99%
“…In order to enhance the photo absorption rate, anti reflection coating (ARC) could be used on the top of the device [28][29][30][31][32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…In a previous work, it was shown that SOI PIN diodes with 80‐nm‐thick silicon undergo a change in the current generation phenomenon due to the influence on the depletion layer by the application of the back‐gate voltage [18]. For a 20‐nm‐thick silicon layer, a greater influence of the back‐gate biasing can be expected due to the greater capacitive coupling of the structure.…”
Section: Back Gate Biasing and Ground Planesmentioning
confidence: 99%